KONSTRUKSI MAKNA BAKUPUKUL MANYAPU BAGI MASYARAKAT MAMALA MALUKU - Sulaeman Sulaeman; Mahdi Malawat; Darma Darma (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Bakupukul manyapu is a ritual whipping each other's limbs to hurt and bleed with healing oils Mamala as nonverbal communication. The purpose of this study is to find and explain the motives, meaning and experience of Mamala society do bakupukul manyapu ritual communication. The research method using the phenomenological method that focuses on the study of meaning bakupukul manyapu ritual communication the perspective Mamala community who experience it. The research uses a qualitative approach based on constructivist paradigm with the technique of collecting data through in-depth interviews, participatory observation, study, library and documentation with supporting data based on Phenomenology perspective, symbolic interaction and social construction theory. The subject is Mamala society the perpetrator bakupukul manyapu with the purposive sampling technique. The result that Mamala society the bakupukul manyapu have a motive "because" that is the motive proud, call, test yourself, and prove, and the motive "for" attention, self-status, self-publication, and self-identity. Bakupukul manyapu experience the pain early, bloody body lashes, whip instead of the mayhem, physical appearance, the blood is dirty, self-confidence, and oil treatment. Bakupukul manyapu meaning is the offering, solicitation, hope, and social solidarity. Meaning construction that bakupukul manyapu is interesting tradition, whipping each other, challenging the local wisdom, confidence, and trust in the conduct of treatment the indigenous Mamala Moluccas of tradition ritual communication.